2019
DOI: 10.1074/jbc.ra119.008209
|View full text |Cite
|
Sign up to set email alerts
|

Interplay of cold shock protein E with an uncharacterized protein, YciF, lowers porin expression and enhances bile resistance in Salmonella Typhimurium

Abstract: Bacterial cold shock proteins (CSPs) function as RNA chaperones. To assess CSP's roles in the intracellular human pathogen Salmonella Typhimurium, we analyzed their expression in varied stress conditions. We found that cold shock protein E (cspE or STM14_0732) is up-regulated during bile salt-induced stress and that an S. Typhimurium strain lacking cspE (⌬cspE) displays dose-dependent sensitivity to bile salts, specifically to deoxycholate. We also found that an uncharacterized gene, yciF (STM14_2092), is up-r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
33
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 28 publications
(50 citation statements)
references
References 71 publications
2
33
0
Order By: Relevance
“…This explained Δ1538 showing a sensitized phenotype to several stress factors, which are likely to be encountered during host infection. Δ1538 displayed reduced survival under bile stress, corroborating with the previously reported role of the KGG family protein YciG [16,51,52].…”
Section: Discussionsupporting
confidence: 89%
“…This explained Δ1538 showing a sensitized phenotype to several stress factors, which are likely to be encountered during host infection. Δ1538 displayed reduced survival under bile stress, corroborating with the previously reported role of the KGG family protein YciG [16,51,52].…”
Section: Discussionsupporting
confidence: 89%
“…Typhimurium 14028 s (WT) was used as the parent strain for all experiments. The ΔcspE strain was reported in an earlier study [15] and the ΔcspA strain was generated similarly and confirmed using primers that are listed in Table S2. The double deletion of cspE and cspA were generated by amplifying the region flanking cspA and electroporating the amplicon into ΔcspE cells harboring pKD46 plasmid (Table S2).…”
Section: Generation Of Single-and Double-gene Deletion Strainsmentioning
confidence: 65%
“…Antibiotics were used at the following concentrations: Ampicillin-100µg ml -1 (HiMedia Laboratories), Chloramphenicol-30 µg ml −1 (HiMedia Laboratories), and Kanamycin-50 µg ml −1 (Sigma Aldrich, Missouri, USA). Arabinose (HiMedia Laboratories) was used at 40 mM for induction of Red recombinase by pKD46 [15].…”
Section: Methods Chemicals Bacterial Strains and Growth Conditionsmentioning
confidence: 99%
See 2 more Smart Citations